2020
DOI: 10.1016/j.eats.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Combined Anterior Cruciate Ligament Primary Repair With an Autograft Reconstruction

Abstract: Anterior cruciate ligament (ACL) reconstruction using an autograft gives good results that could provide improved failure rates. ACL augmentation saving the remnant has demonstrated advantages, such as saving vascular supply and nerve receptors, which could be useful for healing. Conversely, isolated repair techniques are gaining interest but do not give good results because structural augmentation is necessary to reinforce the repair and expect healing. We describe a technique combining the advantages of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The arthroscopically assisted anterior cruciate ligament (ACL) reconstruction has become a prevalent surgical procedure in recent years. [ 1 , 2 ] The number of ACL reconstruction has increased with the development of technology and concept. It is reported that more than 175 thousand primary ACL reconstruction procedures are performed annually in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The arthroscopically assisted anterior cruciate ligament (ACL) reconstruction has become a prevalent surgical procedure in recent years. [ 1 , 2 ] The number of ACL reconstruction has increased with the development of technology and concept. It is reported that more than 175 thousand primary ACL reconstruction procedures are performed annually in the United States.…”
Section: Introductionmentioning
confidence: 99%